Design of a 2 GHz Linear-in-dB Variable-Gain Amplifier with 80-dB Gain Range - Zhengyu Sun; Yuepeng Yan (Active and Passive Electronic Components)
A broadband linear-in-dB variable-gain amplifier (VGA) circuit is implemented in 0.18 μm SiGe BiCMOS process. The VGA comprises two cascaded variable-gain core, in which a hybrid current-steering current gain cell is inserted in the Cherry-Hooper amplifier to maintain a broad bandwidth while covering a wide gain range. Postlayout simulation results confirm that the proposed circuit achieves a 2 GHz 3-dB bandwidth with wide linear-in-dB gain tuning range from −19 dB up to 61 dB. The amplifier offers a competitive gain bandwidth product of 2805 GHz at the maximum gain for a 110-GHz ft BiCMOS technology. The amplifier core consumes 31 mW from a 3.3 V supply and occupies active area of 280 μm by 140 μm.